Arche-speech and Sound Poetry - Braune, Sean (Pivot: A Journal of Interdisciplinary Studies and Thought, 2014)
Steve McCaffery describes sound poetry as a “new way to blow out candles” and “what sound poets do.” In his brief survey of sound poetry, McCaffery describes the genealogy of sound poetry from its earliest formalized birth during Russian futurism (found in the experiments of Khlebnikov and Kruchenykh) and builds his survey until North America, 1978. This essay will consider the history of sound poetry, a history that has no history, but retains the avant-garde experimentalism of modernist poetics. By looking at sound poems by Raoul Hausmann and Kurt Schwitters; the sound-experiments of Diamanda Galás; performance in sound poetry; the influence of “primal therapy” (which emphasizes the therapeutic potential of the scream); and the theological tradition of glossolalia, I will demonstrate how the noisiness and non-sense of sound poetry offers a variety of forms of political engagement against hegemonic uses of sound and silence. Sound poetry is notable in that it is loud – originally being called Lautgedichte or literally “loud poems” – and this brash noise opens up a heterotopic space of acoustic potential: of potential sonic engagement outside of normative chirps, whistles, vocalizations, glottal stops, fricatives, and speech. This “sonic engagement” will be grounded in the new theoretical concept of what I call "arche-speech" or "arche-sound."